Performance of the savonius wind rotor with two inner blades at low tip speed ratio - Al-Ghriybah, Mohanad; Zulkafli, Mohd Fadhli; Didane, Djamal Hissein; Mohd, Sofian (Penerbit Akademia Baru, 2020)
The Savonius wind turbine is considered as one of the solutions for harvesting the kinetic energy from the wind in the urban areas, due to magnificent features such as, low construction cost, high starting torque, and self-starting ability especially at low wind speed. However, the conventional rotor suffers from low efficiency. Thus, modifying the configuration of the rotor may be an effective solution for providing electricity to the communities with no access to the power grid. Thus, this investigation aims to study numerically the effect of adding two inner blades on the performance of the Savonius wind rotor at low tip speed ratios (TSRs). The simulations are carried out using the two-dimensional simulation with the assist of ANSYS software. For turbulence modelling, the K-ε/realizable model was adopted in this study. Power coefficient (Cp) and torque coefficient (Ct) at various TSRs for the rotor are determined under a constant external overlap of 0.018 m. Furthermore, the effect of space between the inner blades was also investigated using three values of spacing. The simulation results show that the rotor with two inner blades performs better than the same rotor without inner blades at all tested TSRs expect at low considered values of 0.2 and 0.25. The heights Cp was 0.188 with 17.1% performance improvement at TSR = 0.4. Furthermore, the numerical results show that Cp values decrease with the decrease of the space between the blades.